ANALISIS PENGANGKATAN KEPALA DAERAH YANG MENYIMPANGI PUTUSAN MK NO 15/PUU-XX/2022 DAPAT MENGGARADASI HUKUM - Gabriel Frans Possenti Masyur Marung; Yusuf Muhamad Said (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
In the elucidation of the Constitution of the Republic of Indonesia, it is emphasized that Indonesia is not based on power (machstaat) but based on rechtsstaat or law. The definition of machstaat includes,